Timor-Leste's Recovery from the 2006 Crisis : Some Lessons - Porter, Doug; Rab, Habib (World Bank, Washington, DC, 2017)
This note looks specifically at how the government used Public Finance Management (PFM) policies to help address the enormous short-term challenges of a fragile situation in the aftermath of the 2006 crisis. The government capitalized on a rapid increase in oil revenues and through administrative measures that delegated more responsibility for spending decisions to line ministries, achieved a rapid increase in the rate of public spending on cash transfers, goods and services and public works. This note starts by summarizing the evolving challenges of the post-independence PFM system, the fragility of 2006/07, and the changed fiscal outlook following the surge in petroleum revenue. It then looks at the government's PFM policies that helped it to address urgent demands and successfully restore short term stability. The note concludes by drawing possible lessons from this period for other post-conflict situations.